The Impact of Corporate Governance Practices On Corporate Growth and Sustainability in Botswana (International Journal of Scientific Research and Management (IJSRM), 2024)
Corporate governance is an essential part of modern corporate strategy and a framework that guarantees accountability, fairness as well transparency in collaboration with the organisation. It governs the corporate performance and sustainability by regulating relationships of management with board, shareholders & stakeholders. Bringing the governance practices of its Botswana member firms in-line with international standards while also meeting local needs is a unique challenge that arises as an emerging market. This study aims to investigate the corporate governance practices such as board diversity, financial disclosure and independent director of a board in promoting further growth in Botswana. Descriptive statistics showed that there were low levels of governance within the sample firms; and many had positive relationships between their different governance factors as well as corporate sustainability and performance. The findings from the regression analysis indicated that board diversity, financial disclosure, and board independence have a significant positive effect on corporate sustainability and performance. These results underline the necessity of implementing effective governance mechanisms in realizing sustainable corporate expansion.